Pengaruh Media Edukasi terhadap Pengetahuan Remaja Putri tentang Anemia: Literature Review - Adyani, Kartika; Apriliana, Shinta Dwi; Susilowati, Endang (Faletehan Health Journal, 2024)
Anemia often occurs in female adolescents, resulting on inhibition of learning concentration, physical activity, decreased anti-bodies, and in a long-term affecting on their pregnancy. One of the causes is the lack of knowledge of maintaining a healthy diet and self-motivation of the importance of balanced nutrition in anemia prevention which is given through several researched educational media. This article aimed to determine the effects of educational media on female adolescent knowledge of anemia. The method of article searches through PubMed and Google Scholar used some keywords, namely anemia, female adolescent, educational media, and knowledge. The searches obtained 7 articles that met the writing criteria. The review results showed that some educational media of anemia can significantly affect the increase in female adolescent knowledge, namely audiovisual educational media, posters, and booklets. The results of the review also proved that the frequently used educational media in counseling is audiovisual media since it is more interesting and has a positive impact on the increase of female adolescent knowledge of anemia. Therefore, health workers should take a role in the efforts of anemia prevention in female adolescents through the provision of educational media.